ZnO photoelectrode simultaneously modified with Cu2O and Co-Pi based on broader light absorption and efficiently photogenerated carrier separation. Issue 10 (12th September 2018) - Ma, Chonghao; Liu, Zhifeng; Cai, Qijun; Han, Changcun; Tong, Zhengfu
Abstract : A ZnO/Cu2 O/Co-Pi photoelectrode is applied in PEC water splitting, improving the light absorption and photogenerated carrier separation. Abstract : Expanding the optical response range and improving the photogenerated carrier separation rate are critical to increasing the efficiency of photoelectrochemical (PEC) water splitting. In this paper, a ZnO/Cu2 O/Co-Pi heterojunction was successfully fabricated for photoelectrochemical (PEC) water splitting. As a narrow band semiconductor, Cu2 O can extend the absorption range of solar spectra. Co-Pi plays the role of a hole-trapping cocatalyst to accelerate the water oxidation reaction at the electrode and electrolyte interfaces. This complex ZnO/Cu2 O/Co-Pi photoanode moves the origin potential in a negative direction, and displays an improved photocurrent density of 1.58 mA cm −2 at 1.23 V vs . RHE, which is 1.08 times that of a ZnO/Cu2 O heterojunction and 2.03 times that of pure ZnO. The efficient PEC performances of the ZnO/Cu2 O/Co-Pi photoanode are caused by the broader light absorption and higher photogenerated carrier separation rate. This study proved that the simultaneous reaction of the heterojunction and cocatalyst has great prospects for application in efficient photoelectrochemical (PEC) water splitting photoelectrode systems.